STRATEGIC ANALYSIS OF THE TRAVEL AGENCY IN THE EDUCATION TOURISM MARKET OF THE CZECH REPUBLIC - Heřmánek, Lukáš; Štěrbová, Ludmila, 1957-; Antonovic, Vladan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
The following master thesis works with literature from education tourism, outlines the global overview of the industry from the perspective of a small travel agency operating on the Czech market offering study abroad packages in Great Britain. In the second part analysis of the Czech market is performed with insights on the relevant metrics influencing education tourism market in the country including its participants. This is followed by an analysis of the UK environment of the education sector focused on the statistics and data related to the internationally mobile students and influence of upcoming Brexit for the company and students in general. Subsequently, analysis of the internal and external environment of the analysed company is performed in the form of PESTL and Porters Value Chain. With the usage of conducted secondary and primary research as well as interviews, SWOT analysis is performed with final recommendations for actions being applied in the upcoming recruitment season 2019/20.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses